Inflammation and peripheral venous disease - Cushman, Mary; Callas, Peter W.; Allison, Matthew A.; Criqui, Michael H. (Thrombosis and Haemostasis, 2014)
The inflammatory response to healing in venous thrombosis might cause vein damage and post-thrombotic syndrome. Inflammation may also be involved in venous insufficiency apart from deep-vein thrombosis. We studied the association of inflammation markers with venous insufficiency in a general population sample. We characterised 2,404 men and women in a general population cohort for peripheral venous disease and its severity using physical exam, symptom assessment, and venous ultrasound. Inflammation markers, C-reactive protein (CRP), fibrinogen, interleukin 1-beta (IL-1-beta), IL-8, IL-10, intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), E-selectin, monocyte chemoattractant-1 (MCP-1) and vascular endothelial cell growth factor (VEGF) were compared in 352 case participants with peripheral venous disease and 352 controls with no venous abnormalities frequency matched to cases by age, sex and race. Associations were also evaluated including a subset of 108 cases of severe venous disease, as previously defined. Odds ratios (95% CI), for peripheral venous disease for biomarkers in the top quartile (adjusting for age, race, sex, body mass index and history of venous thrombosis) were 1.8 (1.1–3.0), 1.6 (1.0–2.5) and 1.5 (0.9–2.3) for CRP, fibrinogen and IL-10, respectively. Associations were larger considering cases of severe venous disease, with odds ratios for these three analytes of 2.6 (1.2–5.9), 3.1 (1.3–7.3) and 2.2 (1.1–4.4), and for IL-8: 2.4 (1.1–5.2). There was no association of IL-1-beta, ICAM-1, VCAM-1, E-selectin, MCP-1 or VEGF with overall cases or severe venous disease. In conclusion, a subset of inflammation markers were associated with increased risk of peripheral venous disease, suggesting potential therapeutic targets for treatment.
Keywords: Inflammation; venous disease; venous insufficiency; risk factor